PEMODELAN POLA PRODUKTIVITAS TANDAN BUAH SEGAR (TBS) BERDASARKAN APLIKASI BEBERAPA AGEN HAYATI TERHADAP HAMA DI PERKEBUNAN KELAPA SAWIT - Salmiyati, Salmiyati; Kuncahyo, Budi (Akta Agrosia, 2022)
Pests are controlled in oil palm plantations by using biological agents to achieve higher productivity of fresh fruit bunches (FFB) of oil palm (Elaeis guineensis Jacq.). This study aims to create a modeling pattern for oil palm FFB productivity based on application data of biological agents at several levels of planting age. The research was conducted in Pelalawan, Riau, namely on young plants, juvenile plants, mature plants and old plants on mineral soil. The data used are the application data of the biological agents Tyto alba, Antigonon leptosus and Turnera subulata. Data were analyzed using Cobb Douglas multiple linear regression and correlation analysis. The results of the regression analysis are used to build a model for predicting FFB productivity patterns using Stella Software. The results of the model regression analysis showed that the coefficient of determination was obtained at 0.265, meaning that together the variables Antigonon leptosus, Tyto alba and Turnera subulata affected FFB productivity by 26.5%. The results of the regression analysis showed that the effect of each Antigonon leptosus, Tyto alba, and Turnera subulata increased by 1%, so FFB productivity increased by 0.018, 0.024, and 0.028%, respectively. The modeling pattern for the development of biological agents shows that FFB productivity will increase and start to decrease at the ages of 14 - 30 years in young, juvenile, mature, and old plants. The total rate of increase from the application of biological agents is 0.047%.